Antibacterial and Antibiofilm Activity of Flaxseed Oil - Al-Mathkhury, Harith Jabbar Fahad; Al-Dhamin , Ahmed Saad; Al-Taie, Khamael Lutfi (Iraqi Journal of Science, 2022)
The present study aimed to explore the antibacterial and antibiofilm activity of flaxseed oil on some locally isolated bacterial pathogens. No inhibitory effect was noticed against Escherichia coli or Enterococcus faecalis. However, variable effects were developed against Methicillin resistant Staphylococcus aureus (MRSA), methicillin sensitive Staphylococcus aureus (MSSA), Klebsiella pneuminae and Staphylococcus epidermidis. The flaxseed exhibited antibiofilm activity against all tested bacterial isolates (MSSA, MRSA, S. epidermidis and K. pneumoniae) and showed various degrees of inhibition against them. Experimental wounds were healed by application of flaxseed oil. In conclusion, flaxseed oil is a good alternative medication can be used to treat wound infection caused by bacteria.